USING WORD BANK TO ENRICH VOCABULARY OF GRADE X STUDENTS OF TAMAN KARYA MADYA VOCATIONAL HIGH SCHOOL - Indira Lusianingtyas Siswanto; Catur Fitriana; Barli Bram (Eltin Journal : Journal of English Language Teaching in Indonesia, 2019)
This paper explored the teaching techniques to enhance the tenth grade students’     vocabulary items in Taman Karya Madya Vocational High School Yogyakarta, Indonesia. The researchers conducted a pre-test before undertaking the classroom action research (CAR) and a post-test to measure the students’ improvement afterwards. Data were analyzed using the qualitative method by comparing the results of the pre-test and of the post-test. This study sought to answer the research questions related to how the word bank helped students in enriching vocabulary and whether there was any relationship between the teaching method applied in this CAR and the students’ improvement in vocabulary mastery. Results indicated that word bank assisted the students in enhancing vocabulary and that it was essential to choose an appropriate technique in teaching vocabulary.